Kantorowicz E. H., The King’s Two Bodies - Adamus, Jan (Czasopismo Prawno-Historyczne, 1960)
Recenzja: Ernst H. Kantorowicz, The King’s Two Bodies, A Study in Mediaeval Political Theology, Princeton University Press, Princeton, New Jersey, 1957, ss. XVI, 567, 24 tablic